ATR-Chk1-APC/CCdh1-dependent stabilization of Cdc7-ASK (Dbf4) kinase is required for DNA lesion bypass under replication stress - Yamada, Masayuki; Watanabe, Kenji; Mistrik, Martin; Vesela, Eva; Protivankova, Iva; Mailand, Niels; Lee, MyungHee; Masai, Hisao; Lukas, Jiri; Bartek, Jiri (Genes & development, 2013)
Cdc7 kinase regulates DNA replication. However, its role in DNA repair and recombination is poorly understood. Here we describe a pathway that stabilizes the human Cdc7-ASK (activator of S-phase kinase; also called Dbf4), its regulation, and its function in cellular responses to compromised DNA replication. Stalled DNA replication evoked stabilization of the Cdc7-ASK (Dbf4) complex in a manner dependent on ATR-Chk1-mediated checkpoint signaling and its interplay with the anaphase-promoting complex/cyclosome(Cdh1) (APC/C(Cdh1)) ubiquitin ligase. Mechanistically, Chk1 kinase inactivates APC/C(Cdh1) through degradation of Cdh1 upon replication block, thereby stabilizing APC/C(Cdh1) substrates, including Cdc7-ASK (Dbf4). Furthermore, motif C of ASK (Dbf4) interacts with the N-terminal region of RAD18 ubiquitin ligase, and this interaction is required for chromatin binding of RAD18. Impaired interaction of ASK (Dbf4) with RAD18 disables foci formation by RAD18 and hinders chromatin loading of translesion DNA polymerase η. These findings define a novel mechanism that orchestrates replication checkpoint signaling and ubiquitin-proteasome machinery with the DNA damage bypass pathway to guard against replication collapse under conditions of replication stress.
Keywords: HeLa Cells; DNA lesion bypass; DNA Damage; replication stress; Cdc7; Cell Line, Tumor; HEK293 Cells; CD antigeny; Checkpoint Kinase 1; vazba proteinů; nádorové buněčné linie; lidé; HeLa buňky; geny APC; proteinkinasy; replikace DNA; Protein Serine-Threonine Kinases; signální transdukce; checkpoint kinasa 1; Protein Binding; ATM protein; Signal Transduction; HEK293 buňky; Antigens, CD; Cell Cycle Proteins; poškození DNA; RAD18; Genes, APC; Chk1; Ataxia Telangiectasia Mutated Proteins; Cadherins; Protein Kinases; Enzyme Stability; DNA Replication; kadheriny; proteiny buněčného cyklu; APC/CCdh1; protein-serin-threoninkinasy; stabilita enzymů; Humans